Developing an Augmented Reality Chemistry Textbook on Acids and Bases with Ethnochemistry to Enhance Students Understanding of Chemical Representations - Ariani, Sunniarti; Supriadi, Supriadi; Ardiyanti, Yunita; Hidayah, Weny Amanatul; Daraswita, Adina Ayu (Jurnal Pijar Mipa, 2025)
This development research presents an Augmented Reality(AR)-based textbook that integrates chemical concepts with the SASAMBO culture, highlighting an innovative approach to ethnochemistry. The study aims to produce a practical, valid, and effective AR textbook to enhance students’ understanding of chemical representations. The research follows the 4D development model: Define, Design, Develop, and Disseminate. The textbook was validated by two experts and tested for effectiveness with a limited implementation involving 26 students. Data were collected using validation and practicality questionnaires, as well as pretest-posttest evaluations. Validation data were analyzed using Aiken’s V, while improvements in students’ understanding were assessed with a paired t-test via IBM SPSS Statistics 25. Results show high validity (Aiken’s V = 0.9), strong practicality (86% average score), and a significant increase in understanding (t = 16.871, p < 0.005). These findings suggest that the AR-based textbook is a valid, practical, and effective tool for enhancing students’ comprehension of chemical representation.